Phytochemical Screening and Antimicrobial Activity of Phyllanthus Amarus Leaves (Stone Breaker) Against Some Selected Microorganisms - Lawan, Imrana; Suwaiba Abba Ismail; Aminu Baita; Zeenatu Ali Baba (CV Media Inti Teknologi, 2026)
BACKGROUND: Phyllanthus amarus is among the most significant medicinal plants found in tropical and subtropical regions, commonly used in the treatment of diseases affecting the stomach, liver, kidneys, and spleen. This study aimed to identify the phytochemical constituents and evaluate the antimicrobial activities of the leaves of Phyllanthus amarus METHOD: The powdered leaf sample was extracted using ethanol at a sample-solvent ratio of 1:3. The resulting crude extract was then fractionated using four different solvents: petroleum ether, chloroform, acetone, and methanol. Each of the four fractions was subsequently subjected to phytochemical screening and antimicrobial activity evaluation. RESULTS: The results indicated that the plant leaves contained all the phytochemicals tested. The petroleum ether fraction showed the presence of all the phytochemical constituents. The chloroform fraction contained alkaloids, saponins, polyphenols, and glycosides only. The acetone fraction exhibited all the phytochemicals except saponins, polyphenols, and terpenoids, while the methanol fraction contained alkaloids, steroids, polyphenols, and glycosides. Antimicrobial analysis revealed zones of inhibition against the tested organisms, with the chloroform fraction demonstrating the highest activity. These findings suggest that the plant possesses both physiological and medicinal significance for humans, consistent with previous research reports CONCLUTION: The antimicrobial evaluation of four fractions showed zones of inhibition on the tested organisms, which verified their uses in the treatment of various ailments may be attributable to some of its phytochemical constituents with high drug properties.